Serum exosomal miR‐16‐5p functions as a tumor inhibitor and a new biomarker for PD‐L1 inhibitor‐dependent immunotherapy in lung adenocarcinoma by regulating PD‐L1 expression - Chen, Hua‐Lin; Luo, Yi‐Ping; Lin, Mu‐Wen; Peng, Xiao‐Xia; Liu, Mei‐Liang; Wang, Yong‐Cun; Li, Shu‐Jun; Yang, Dong‐Hong; Yang, Zhi‐Xiong (Cancer medicine (Malden, MA), 2022)
Objectives We aimed at investigating whether serum exosomal miR‐16‐5p could be utilized as an immunotherapy biomarker in lung adenocarcinoma (LUAD) patients administered by programmed cell death ligand‐1 (PD‐L1) inhibitors, and to evaluate its functions in LUAD progression. Methods Sixty LUAD sufferers and 20 healthy controls (HCs) were covered in this work. We applied both IHC and WB to examine PD‐L1 level in clinical tissue samples and utilized WB to quantify PD‐L1 expression in LUAD cells and LUAD xenograft tissues, respectively. Transmission electron microscopy (TEM), WB, and nanoparticle tracking analysis (NTA) were executed to confirm the exosomes isolated from serum specimens and cell culture media. To quantify of exosomal miR‐16‐5p level from serum and culture medium of cultured cell, qRT‐PCR experiment was utilized. The connection between tissue PD‐L1 level and serum exosomal miR‐16‐5p expression in PD‐L1‐positive sufferers administered by PD‐L1 inhibitors was verified using Spearman correlation coefficient analysis. In addition, the overall survival (OS) and progression‐free survival (PFS) rates among PD‐L1 inhibitor managed sufferers were acquired through a follow‐up visit. Finally, we used a group of assays, including 5‐bromo‐2′‐dexoyuridine (BrdU) and colony formation test, wound healing experiment, flow cytometry, and nude mice xenograft experiment, to explore the functions of circulating exosomal miR‐16‐5p on LUAD cell proliferation, apoptosis, and migration, as well as tumor development, respectively. Results PD‐L1 expression was positively related to T stage (tumor size stage), and PD‐L1 inhibitor treatment reduced the PD‐L1 expression and mitigated T stage in PD‐L1‐positive LUAD sufferers. For PD‐L1‐positive LUAD sufferers, elevated PD‐L1 expression or reduced serum exosomal miR‐16‐5p level were linked to longer PFS and OS upon PD‐L1 inhibitor treatment. The number of exosomes in patient's serum was more than that in the serum of healthy individuals, and PD‐L1 inhibitor treatment decreased the number of serum‐derived exosomes in PD‐L1‐positive LUAD sufferers. Exosome‐derived miR‐16‐5p was downregulated in patient's serum and cell culture medium, and this was negatively linked to tumor stage and PD‐L1 expression. Meanwhile, PD‐L1 inhibitor treatment could increase the serum exosomal miR‐16‐5p expression, and the expression change of serum exosomal miR‐16‐5p was diametrically related to PD‐L1 after the treatment. Moreover, the overexpression of PD‐L1 accelerated tumor growth and decreased the exosomal miR‐16‐5p content in cell culture media, while exosomal miR‐16‐5p overexpression in cell culture media inhibited tumor development by decreasing the PD‐L1 expression. Exosomal miR‐16‐5p overexpression in cell culture media also depressed LUAD cell proliferation and migration, and stimulated cell apoptosis, especially in the cells which cultured in the mediums with PD‐L1 inhibitor in vitro. Conclusions Serum exosomal miR‐16‐5p may be a latent tumor inhibitor and a new biomarker for PD‐L1 inhibitor‐dependent immunotherapy in LUAD by regulating the PD‐L1 expression. 1.Exosomal miR‐16‐5p was downregulated in human LUAD serum samples and cell culture media. 2.Serum exosomal miR‐16‐5p was related to the tumor size stage and PD‐L1expression of LUAD patients. 3.Overexpression of exosomal miR‐16‐5p repressed cell proliferation and migration, stimulate cell apoptosis, and restrain tumor growth by lowering the PD‐L1 expression.